Using Open-Source Data to Study Bias Homicide Against Homeless Persons - Gruenewald, Jeff A. (International Journal of Criminology and Sociology, 2013)
Despite their high-profile nature, there has been a lack of scholarly research on bias-motivated homicide in the United States. One explanation for this dearth of prior research is the lack of official data available on this type of crime. In response, the current study proposes an alternative method for studying one form of bias crime, homicides targeting homeless persons, using open-source data (e.g., court documents, news media reports, advocacy group chronologies, etc.). To demonstrate their utility, open-source data are employed to empirically examine anti-homeless homicide incident, suspect, and victim characteristics. Findings reveal that anti-homeless homicide tends to be committed in public parks with blunt objects by groups of young males against older, solitary male victims. Implications for policy are briefly discussed.